2012
DOI: 10.3810/hp.2012.04.970
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Properties of Berberine: From Cellular Pharmacology to Clinical Effects

Abstract: Berberine is an alkaloid that is highly concentrated in the roots, rhizomes, and stem bark of various plants. It affects glucose metabolism, increasing insulin secretion, stimulating glycolysis, suppressing adipogenesis, inhibiting mitochondrial function, activating the 5' adenosine monophosphate-activated protein kinase (AMPK) pathway, and increasing glycokinase activity. Berberine also increases glucose transporter-4 (GLUT-4) and glucagon-like peptide-1 (GLP-1) levels. On GLP-1 receptor activation, adenylyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Berberine, an alkaloid, has been reported to have anti-diabetic activity [36], [37]. Moreover, a direct action of berberine on carbohydrate metabolism in the intestine has been suggested in the recent studies [38][41]. Short-term clinical trials have also confirmed the anti-diabetic and insulin-sensitizing effect of berberine [38].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine, an alkaloid, has been reported to have anti-diabetic activity [36], [37]. Moreover, a direct action of berberine on carbohydrate metabolism in the intestine has been suggested in the recent studies [38][41]. Short-term clinical trials have also confirmed the anti-diabetic and insulin-sensitizing effect of berberine [38].…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms such as increasing insulin sensitivity, modulating gut microbiota, activating the adenosine AMPK pathway, promoting intestinal glucagon‐like protein‐1 secretion, stimulating glycolysis in peripheral tissue cells, inhibiting gluconeogenesis in liver, increasing glucose transporter, and upregulating hepatic low‐density lipoprotein receptor mRNA expression have been proposed for antidiabetic activity of berberine (Vuddanda et al ., ; Xiao et al ., ; Derosa et al , ). Regarding there are more than ten review articles about berberine and diabetes (Cicero and Tartagni, ; Dong et al ., ; Pang et al ., ), we refer the readers to those papers.…”
Section: Endocrine Effectsmentioning
confidence: 97%
“…This antidiabetic and insulin sensitizing effect of berberine has been confirmed in a few relatively small, short-term clinical trials [29]. To date, very few reports on the lipid regulation by the other alkaloids derived from CAE have been published.…”
Section: Discussionmentioning
confidence: 83%